Evolution, through participation in a research group, of Mozambican secondary school teachers' personal relation to limits of functions - Huillet, Danielle Jeanne Georgette (My University, 2008)
This study investigates the evolution of four Mozambican teachers’ personal relation to the limit concept through their participation in a research group, where they looked at mathematical issues concerning several aspects of the limit concept. It shows how the teachers’ early personal relation to limits was close to the Mozambican Secondary School institutional relation to this concept, and how it evolved to a more elaborate relation. This evolution is shown to be uneven and limited for some aspects of mathematics for teaching limits which require deep understanding of basic mathematical concepts. This study also provides an analysis of the teachers-as-researchers movement, where teachers’ research mainly focuses on pedagogical issues, taking the mastery of mathematical knowledge for granted. It illustrates the difficulties faced by a teacher when challenging, not only his pedagogical practice, but also the mathematical content of his teaching. It concludes that this kind of research should be centred on mathematics.